The determinants of economic growth in Algeria, Empirical evidence through the ARDL approach - HOCINE BELHIMER; KAMEL HELALI (Journal of Excellence for Economics and Management Research, 2023)
The purpose of this empirical study is to investigate the factors that determine economic growth in Algeria, specifically by incorporating financial variables from endogenous growth models. The Autoregressive Distributed Lag model was utilized to analyze three types of variables - financial, financial instabilities, and control - from 1965 to 2019. The results indicate that inflation has a positive correlation with growth in Algeria in both the short and long term, while an improvement in the M2/GDP ratio promotes growth in the short term. However, this effect diminishes in the long term, possibly due to the consumption structure of the Algerian economy. Additionally, the study confirms the existence of an error correction mechanism in the long term, with economic growth correcting to 91.1%.